Pengaruh Media Sosial dan QRIS (Quick Response Code Indonesian Standard) Terhadap Peningkatan Penjualan UMKM di Kecamatan Dampit Kabupaten Malang - Enjelita, Yayang; Priyono, Achmad Agus; Millaningtyas, Restu (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to analyze the influence of social media and QRIS on increasing sales of Micro, Small, and Medium Enterprises in Dampit District, Malang Regency. Social media is used as a promotional tool that can reach a wider range of consumers, while QRIS facilitates non-cash transactions quickly and efficiently. The method used is a quantitative approach by distributing questionnaires to Micro, Small, and Medium Enterprises actors. The sampling technique was applied with purposive sampling, with a sample size of 75 respondents. Data analysis was carried out using multiple linear regression. The results of the simultaneous test (F test) show that the use of social media and QRIS has a positive and significant effect on increasing sales of Micro, Small, and Medium Enterprises. While the partial (t test) shows that social media and QRIS have a significant positive effect on increasing sales. This second factor helps Micro, Small, and Medium Enterprises in expanding the market and increasing consumer convenience in transactions. Keywords: Social Media, QRIS, Micro, Small, and Medium Enterprises, Sales